2019
DOI: 10.1177/0276237419868952
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Music Listener Motivations: The Neglected Values

Abstract: Considerable research on music psychology indicates correlations between musical preferences and individual differences in personality, between the various uses of music and personality traits, and between musical preferences and personal values. However, the association between personal values and the multiple ways in which music is used has not been considered yet. To investigate this issue, 400 participants completed a self-report questionnaire comprising the uses of music, personality traits, and personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The influence of music on mood, through emotions and emotional states, is considered one of the most common reasons for listening to music (Juslin and Sloboda, 2011). According to Manolika et al (2021), the emotional and social use of music is predicted by gender. In the case of experimenting with positive emotions and escaping from the routine (such as stress reduction) and socialising with other people, women are more predisposed to listen to music than men.…”
Section: Sociodemographic Profile Of the Tourist Interested In Musicmentioning
confidence: 99%
“…The influence of music on mood, through emotions and emotional states, is considered one of the most common reasons for listening to music (Juslin and Sloboda, 2011). According to Manolika et al (2021), the emotional and social use of music is predicted by gender. In the case of experimenting with positive emotions and escaping from the routine (such as stress reduction) and socialising with other people, women are more predisposed to listen to music than men.…”
Section: Sociodemographic Profile Of the Tourist Interested In Musicmentioning
confidence: 99%
“…Several studies have classified the purposes of using music into various categories [ 6 , 8 , 9 ]. However, in the present study, “using music” does not only refer to listening to music, but also to various human activities such as portraying a particular image to others by making them listen to music.…”
Section: Methodsmentioning
confidence: 99%
“…Although the classification pattern partially differs among these studies [ 6 , 8 , 9 ], Lonsdale and North [ 8 ] indicate that purposes of using music can be classified into six categories ( positive mood management, negative mood management, diversion, interpersonal relationships, personal identity , and surveillance ). We adopted this classification partially in our study, because it is popular and often used for reference.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that both values and uses of music have been related to musical preferences (e.g., Chamorro-Premuzic & Furnham, 2007; Gardikiotis & Baltzis, 2012), and that uses of music vary as a function of values (Manolika, Baltzis, & Gardikiotis, 2021), we expect that uses of music may mediate, at least in part, the association between a person’s values and his or her preferences for specific types of music. To be specific, previous research in the psychology of aesthetics has consistently found that the more intellectually curious and creative people are, the more likely they are to appreciate the arts and experience music intellectually (e.g., Silvia, Fayn, Nusbaum, & Beaty, 2015).…”
Section: Aim Of the Present Study And Hypothesesmentioning
confidence: 99%